2019
DOI: 10.3390/app9030589
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Electromyography Test for the Analysis of the Aerobic-Anaerobic Transition in Elite Cyclists during Incremental Exercise

Abstract: (1) Background: The aim of this study was to investigate the validity and reliability of surface electromyography (EMG) for automatic detection of the aerobic and anaerobic thresholds during an incremental continuous cycling test using 1 min exercise periods in elite cyclists. (2) Methods: Sixteen well-trained cyclists completed an incremental exercise test (25 W/1 min) to exhaustion. Surface bipolar EMG signals were recorded from the vastus lateralis, vastus medialis, biceps femoris, and gluteus maximus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Electromyography (EMG) is an electrical signal generated by skeletal muscles when they contract spontaneously [ 2 ]. EMG signal analysis can provide continuous measurement of the muscle’s state during the continuous fatigue contraction process, which is different from the subjective typical assessment that usually indicates that the subject can no longer perform the test [ 3 ]. The surface electromyography signal (sEMG) is a comprehensive effect of superficial muscle EMG and nerve trunk electrical activity on the skin surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromyography (EMG) is an electrical signal generated by skeletal muscles when they contract spontaneously [ 2 ]. EMG signal analysis can provide continuous measurement of the muscle’s state during the continuous fatigue contraction process, which is different from the subjective typical assessment that usually indicates that the subject can no longer perform the test [ 3 ]. The surface electromyography signal (sEMG) is a comprehensive effect of superficial muscle EMG and nerve trunk electrical activity on the skin surface.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have studied muscle fatigue recognition models that can identify muscle fatigue states by detecting changes in sEMG signals. Latasa et al detected the EMG signals of cyclists in an incremental continuous cycling test and used a multi-segment linear regression algorithm to study the aerobic-anaerobic threshold transition [ 3 ]. Martinez et al recorded the subjects’ sEMG signals in the fatigue state of the vastus lateralis in the incremental cycling test and analyzed the correlation between muscle fiber conduction velocity (MFCV), instantaneous mean frequency (iMNF), normalized root mean square (RMS), and muscle fatigue state [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, SI was associated with higher mechanical and metabolic stress in muscle tissue than LI, as deduced from its higher power output (14% higher than LI) and its prolonged time above 90% of VO 2max (54%). It was thus surprising that SI was not associated with increased EMG activity, as expected from previous studies 17,40 . This discrepancy may be due to numerous factors, including the higher pedaling frequency in SI compared to LI, the short breaks (15 seconds) between short work interval (30 seconds), the relative small differences in power output between SI and LI (90% vs 80% of W max ), and the small sample size in EMG measurements (n = 6 ).…”
Section: Discussionmentioning
confidence: 58%
“…It was thus surprising that SI was not associated with increased EMG activity, as expected from previous studies. 17,40 This discrepancy may be due to numerous factors, including the higher pedaling frequency in SI compared to LI, the short breaks (15 seconds) between short work interval (30 seconds), the relative small differences in power output between SI and LI (90% vs 80% of W max ), and the small sample size in EMG measurements (n = 6). In SI, the increased time above 90% of VO 2max was likely due to the combination of increased intensity during work intervals and the sustained elevation of VO 2 during 15-seconds active pauses.…”
Section: Discussionmentioning
confidence: 99%
“…During early research, authors confirmed the importance of using the EMG FT point in both recreational and professional athletes to assess exercise intensity and fatigue [ 21 ]. However, up to this point, few papers completely suggested the replacement of the means of measuring and determining the ventilatory thresholds by using the EMG method [ 22 ].…”
Section: Discussionmentioning
confidence: 99%